Urgensi Manajemen Humas di Pondok Pesantren - Dessi Asdrayany; Machdum Bachtiar; Ahmad Qurtubi (Departement of Mathematics Education, 2024)
Islamic boarding schools are one of the oldest Islamic educational institutions in Indonesia. With the presence of Islamic boarding schools, of course they must meet the needs of the community in an area. Public Relations is present as a contact person for Islamic boarding schools with the community. By implementing public relations management in Islamic boarding schools, programs related to the community can be implemented well. The aim of this research is to examine the urgency of public relations management in Islamic boarding schools. The method used is a qualitative method with a literature review approach. Data sources were obtained from several books and journals. Research findings show that public relations plays an important role as a problem solver, communication facilitator, expert advisor, process facilitator, and communication technician in the struggle to maintain Islamic boarding school operations.